PENGARUH LOKASI (PLACE) DAN HARGA (PRICE) TERHADAP LOYALITAS PENGUNJUNG OBJEK WISATA ZIARAH SITU LENGKONG PANJALU - Iin Handayani; Wilma Zuarko Adji (JEBS (Journal of Economic and Business Student), 2022)
This research aims to find out the extent of the influence of location and price on the loyalty of visitors to the pilgrimage attraction Situ Lengkong Panjalu, as well as the obstacles that arise and the efforts that must be made.This research uses quantitative methods. Data collection techniques using questionnaires. The data analysis technique uses classic assumption tests, coefficient determination tests and correlation coefficients using SPSS 26.Based on the calculation of location correlation value of 0.877 shows that there is a very strong influence relationship between location variables and visitor loyalty variables. The price correlation value of 0.687 indicates that there is a strong influence relationship between price variables and visitor loyalty variables. The value of the determination coefficient is 77% of this indicates that location and price affect visitor loyalty by 77% and the remaining 23% are influenced by other factors that are not studied. As for the obstacles faced in this study, the trash can is not good, so the area around the trash can is not neat and there are not yet electronic payment tools available. Efforts to address this can improve the garbage can in the tourist area and provide electronic payment equipment. The conclusion that location and price have a very strong relationship to the loyalty of visitors with a high level of influence. Keywords : Place, Price and Loyalty of Visitors